KEDUDUKAN ASET DIGITAL DALAM KEWARISAN PERSPEKTIF HUKUM PERDATA - Nadela Nurima; Mairul Mairul (Journal of Indonesian Comparative of Syari'ah Law, 2025)
The digital transformation has introduced new forms of wealth in the form of digital assets, such as cryptocurrency, NFTs, e-wallets, and social media accounts. The existence of these assets raises legal challenges in the context of inheritance law in Indonesia, since the Indonesian Civil Code (KUHPerdata) does not explicitly regulate them. This study aims to analyze the legal status of digital assets as inheritance objects and evaluate the mechanisms of their transfer under Indonesian civil law. The research employs a normative juridical method with statutory, conceptual, and comparative approaches. The findings reveal a legal vacuum that causes uncertainty for heirs, particularly due to the discrepancy between the Civil Code provisions and the privacy policies of global digital platforms. This study recommends a progressive interpretation of Articles 499, 503, 830, 832, and 833 of the Civil Code to include digital assets as inheritance objects, as well as the establishment of national regulations governing digital inheritance, including digital wills and the appointment of digital executors. Thus, the study is expected to contribute both academically and practically to the development of inheritance law in Indonesia, making it more adaptive to technological advancements.